Legal education and judicial training in Europe : the menu for justice project report - Piana, Daniela (Eleven International Pub., 2013)
The Menu for Justice project - funded with support from the European Commission - is the first European project that takes seriously the issue of how a new generation of Europeans should be trained in law and legal matters, as well as how experts in law and the judicial process can develop new skills and competences to effectively face the challenges of a common judicial space. The project takes up a major issue in contemporary judicial politics: to what extent and by which means can legally relevant expertise be supported to ensure an efficient, effective, and legitimate judicial system? This.